Student’s reflection on environmental conservation: the level of knowledge, attitude, and behavior - Mohamad, Mimi Mohaffyza; Rosli, D.I.; Abdullah, Nurul Hidayah Liew; M. Nusa, F.N.; Ahmad, A. (Innovare Academics Sciences PVT. LTD, 2020)
The purpose of this paper is to identify the reflection of primary school students’ in term of their environmental conservation awareness based on their knowledge, attitude, and behavior. The survey method was used in data collection and the questionnaire was distributed to 235 students from 25 different school under UTHM’s Knowledge Transfer Program in Kluang District. The results obtained moderate-average level of environmental awareness for each construct (i.e. knowledge, attitude, behaviour). The analysis suggest level of reflection has significant effect on gender and race differences for certain construct, however, it is positive correlation between the level of environmental conservation’s reflection with demographics profile. This study offers new insights into the impact of education on environmental protection, the need for environmental education to improve conservation awareness.